Disability and the media - Ellis, Katie, 1978-; Goggin, Gerard, 1964- (London Palgrave, 2015)
"An approachable but critical introduction to the complex relationship between disability and the media, bringing together prominent theoretical work and research on disability internationally, with analysis and examples of a range of contemporary media issues in news, the press, broadcasting and new media"--
Machine generated contents note: -- 1. Introduction: Why Does Disability Matter for Media? -- 2. Understanding Disability and Media -- 3. Media's Role in Disability -- 4. The News on Disability -- 5. Beyond Disabled Broadcasting -- 6. Disability and Media Work -- 7. Conclusion: Doing Justice to Disability and Media.
Includes bibliographical references (pages 124-145) and index.
Keywords: People with disabilities in mass media; Sociology of disability; SOCIAL SCIENCE / Popular Culture; SOCIAL SCIENCE / People with Disabilities; SOCIAL SCIENCE / Media Studies